(untitled) (Research, Society and Development, 2024)
The present study addresses asthma as a chronic inflammatory disease of the airways, highlighting its symptoms, diagnosis and management, especially in children. The importance of early diagnosis is highlighted, which can be challenging in children under 5 years of age, and the associated risk factors. Asthma is a globally prevalent condition, affecting millions of people and having a significant impact on quality of life and medical resources. Exacerbation of the disease is a common pediatric emergency, requiring rapid and appropriate treatment, including the use of oxygen, ß2 agonists and systemic corticosteroids. From this comes the importance of magnesium sulfate as a therapeutic option in cases of failure of standard therapy, as it helps with bronchodilation and reducing the severity of asthma. Therefore, the conditions for using magnesium sulfate, its dosage and possible side effects will be discussed, emphasizing the importance of monitoring serum magnesium levels during treatment.